Essays on environmental economics and the political economy of inequality - Sant'Anna, André Albuquerque (2018)
Tese (doutorado) - Universidade Federal do Rio de Janeiro, Instituto de Economia, Programa de Pós-Graduação em Economia da Indústria e Tecnologia, 2018. Do natural disasters lead to electoral sanctions? -- Land inequality and deforestation in the Brazilian Amazon -- The threat of communism during Cold War: a constraint to income inequality / André Albuquerque Sant’Anna, Leonardo Weller. Bibliografia: p. 127-147